Government and Non-Government Responses during current situation of COVID-19 Pandemic in India - Sharma, Dheeraj; Joshi, Poonam (Archives of Community Medicine and Public Health, 2021)
It is not easy to recover the damage. India is now the second top country in the world in terms of total COVID-19 infection and recovering from COVID-19 infections. There have been comparatively lesser mortalities despite the high population of the country; which might be because of the predominant younger population, antibodies against the dengue virus, under-reporting of figures, and poor death reporting mechanism. The low testing rate of COVID-19 in India and dependency on the Rapid Antigen Test in some states have been a major downside. Reporting fast recovery of the cases and poor level protocol for testing have allowed the infection to go undetected and spread the disease. The pandemic has resulted in negative socioeconomic impacts in the form of deflation in GDP, unemployment, poverty, recession, and decreased global trade. Though the Government of India has taken plenty of measures to combat the situation, there are still many areas where improvement is possible. The World Health Organization is functioning in collaboration with the Government of India and is providing technical support to the other national Government bodies. Some states did well to control the coronavirus disease, while others could not properly deal with the emergent situation within time. India has promptly and adroitly managed the pandemic situation to an extent.